2021
DOI: 10.54386/jam.v23i4.146
|View full text |Cite
|
Sign up to set email alerts
|

Phenological behaviour of gobhi sarson (Brassica napus L.) and thermal indices as influenced by drip irrigation and fertigation schedules under semi-arid subtropical condition of Punjab

Abstract: A field experiment was conducted during rabi 2016-17 and 2017-18, at the Research Farm of Department of Agronomy, Punjab Agricultural University, Ludhiana, to study the phenological behaviour of gobhi sarson (Brassicanapus L.) and thermal indices as influenced by drip irrigation (60, 80 and 100% of cumulative pan-evaporation, CPE) and fertigation schedules (60, 80 and 100 % recommended dose of fertilizers, RDF) in comparison with conventional flood irrigation and manual application of fertilizers i.e. absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Since the environment is changing daily, sowing windows have a profound influence on both the growth and yield of the crop (Iizumi and Ramankutty, 2015). Sharma et al (2021) reported that delayed sowing reduced the hybrid maize yield by about 55% under rainfed conditions, whereas yield reduction was only 21% in irrigated condition. The reduction in the accumulation of heat units was due to a reduction in the number of days taken to attain the physiological maturity of crop.…”
Section: Introductionmentioning
confidence: 99%
“…Since the environment is changing daily, sowing windows have a profound influence on both the growth and yield of the crop (Iizumi and Ramankutty, 2015). Sharma et al (2021) reported that delayed sowing reduced the hybrid maize yield by about 55% under rainfed conditions, whereas yield reduction was only 21% in irrigated condition. The reduction in the accumulation of heat units was due to a reduction in the number of days taken to attain the physiological maturity of crop.…”
Section: Introductionmentioning
confidence: 99%